Photosynthetic pigments and vigour of rice (Oryza sativa L.) seedlings as affected by kinetin and prohexadione-calcium - Pal, Mamta; Thind, S K (ORYZA-An International Journal of Rice, 2019)
In the present study effects of exogenous application of Kinetin (Kn @ 10, 20 and 40 mg/l) and Prohexadionecalcium (BX-112 @ 5, 10 and 20 mg/l) were studied on rice (Oryza sativa L.) cultivars viz PB-2, PB-3 and PUSA-112. Different levels of Kn and BX-112 were applied to seedlings, five days after sowing (DAS). The content of photosynthetic pigments (total chlorophyll) was recorded at fourteen DAS stage, furthermore application of Kn significantly improved it in selected cultivars with more percent increase at 7 DAS. The content of accessory pigments (carotenoids) was recorded higher in both Kn as well as BX-112 treated sets. Kn application promoted vigour of rice seedlings in the selected cultivars with more pronounced effect in treatments involving higher concentration of Kn. BX-112 decreased both the vigour and relative growth rate (RGR) that led to reduction in growth of seedlings of all the three cultivars. This study revealed that though both Kn and BX-112 improved accumulation of photosynthetic pigments yet Kn application promoted growth and vigour of the seedlingswhile BX-112displayed an inhibitory effect on vigour of rice seedling.